Pusat Informasi Pariwisata sebagai Media Pemasaran Berbasis Budaya - Sri Indrahti (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
Tourism in the current development is part of industrial activities, because it involves and influences the emergence of new business units around tourist sites. In this regard, tourism marketing seems to be an important thing that needs attention, especially through culture. Utilizing interesting cultural values to be developed then conveyed to tourists through true and adequate information. The tourism information center needs to be well managed, equipped with sources of information relevant to the location of tourist visits. The writing of this article is based on the results of research on the packaging of local cultural values in pilgrimage tours in Kudus so that it prioritizes a cultural approach. Although it also takes into account the benefits that can be enjoyed by the community as a subject in tourism itself, preserving and maintaining cultural values that contain local wisdom.